Investigating molecular basis of lambda-cyhalothrin resistance in an Anopheles funestus population from Senegal. Issue 1 (December 2016) - Samb, Badara; Konate, Lassana; Irving, Helen; Riveron, Jacob; Dia, Ibrahima; Faye, Ousmane; Wondji, Charles
Abstract Background Anopheles funestus is one of the major malaria vectors in tropical Africa, notably in Senegal. The highly anthropophilic and endophilic behaviours of this mosquito make it a good target for vector control operations through the use of insecticide treated nets, long-lasting insecticide nets and indoor residual spraying. However, little is known about patterns of resistance to insecticides and the underlying resistance mechanisms in field populations of this vector in Senegal. Methods Here, we assessed the susceptibility status ofAn. funestus populations from Gankette Balla, located in northern Senegal and investigated the potential resistance mechanisms. Results WHO bioassays indicated thatAn. funestus is resistant to lambda-cyhalothrin 0.05 % (74.64 % mortality), DDT 4 % (83.36 % mortality) and deltamethrin 0.05 % (88.53 % mortality). Suspected resistance was observed to permethrin 0.75 % (91.19 % mortality), bendiocarb 0.1 % (94.13 % mortality) and dieldrin 4 % (96.41 % mortality). However, this population is fully susceptible to malathion 5 % (100 % mortality) and fenitrothion 1 % (100 % mortality). The microarray and qRT-PCR analysis indicated that the lambda-cyhalothrin resistance in Gankette Balla is conferred by metabolic resistance mechanisms under the probable control of cytochrome P450 genes among which CYP6M7 is the most overexpressed. The absence of overexpression of the P450 gene, CYP6P9a, indicates that the resistance mechanism in Senegal is different to that observed in southern Africa. Conclusions This study represents the first report of pyrethroid and DDT resistance inAn. funestus from Senegal and shows that resistance to insecticides is not only confined toAn. gambiae as previously thought. Therefore, urgent action should be taken to manage the resistance in this species to ensure the continued effectiveness of malaria control.